COMPARISON OF OSTEOGENIC AND CHONDROGENIC DIFFERENTIATION POTENTIAL BETWEEN WHARTON’S JELLY AND ADIPOSE TISSUE MESENCHYMAL STEM CELLS AS THE ALTERNATIVES OF BONE MARROW MESENCHYMAL STEM CELLS: A SYSTEMATIC REVIEW - Petrus Aprianto (Journal of Global Pharma Technology, 2017)
Introduction. Currently, Bone Marrow is the most common source of Mesenchymal Stem Cell (MSC). The limitation of the source and pain post harvesting procedure make the next alternative of BM-MSC is needed. Wharton Jelly, offer a low cost and pain free collection method. Adipose tissue provide abundant amount stem cell and has a interestingly compatible osteogenic and chondrogenic activity. The objective of this study is to search alternative Bone Tissue Engineering (BTE) source other than BM-MSC.Materials and Method. Literature search was conducted using several search engines. This review used all In vitro experimental comparison of Adipose Tissue Mesenchymal Stem Cells (AT-MSC) and wharton’s jelly stem cell (WJ-MSC). We compared osteogenic and chondrogenic differentiation potential between these MSCs. The group of comparison is divided into two sub groups, animal MSCs and human MSCs.Result and Discussion. The first study that compared osteogenic and chondrogenic differentiation from animal AT-MSC and WJ-MSC consists of 7 trials. Most of the result shows that AT-MSC has greater osteogenic differentiation potential compared to WJ-MSC and controversial result for chondrogenic differentiation between them. The second study consist of 3 trials. In these studies, the results were more homogenous and concluded that AT-MSC has higher osteogenic differentiation potential than WJ-MSC but the chondrogenic differentiation were not significantly different.Conclusion. AT-MSC may be more appropriate than WJ-MSC for osteogenesis and bone repair usage.Keyword: Osteogenic differentiation, Chondrogenic differentiation, Wharton’s jelly Mesenchymal Stem Cells, Adipose Tissue Mesenchymal Stem Cells